A prospective clinical study of the implications of IL-8 in the diagnosis, aggressiveness and prognosis of prostate cancer. (15th November 2017) - Roumeguère, Thierry; Legrand, Francois; Rassy, Elie El; Kaitouni, Mehdi Idrissi; Albisinni, Simone; Rousseau, Alexandre; Vanhaeverbeek, Michel; Rorive, Sandrine; Decaestecker, Christine; Debeir, Olivier; Boudjeltia, Karim Zouaoui; Aoun, Fouad
Aim: We evaluated the relationship between IL-8 and prostate cancer (PCa) with emphasis on diagnosis, aggressiveness and prognosis.Materials & methods: Prostate-specific antigen (PSA) and serum IL-8 were collected from patients undergoing prostate biopsy. IL-8 expression was evaluated on immunohistochemistry with IL-8 labeling index. Complete follow-up of this cohort was achieved over a period of up to 6 years with continuous follow-up of PSA levels.Results: Among 135 patients, serum IL-8 level did not correlate to the diagnosis or aggressiveness of PCa. In 52 radical prostatectomy specimens, a higher IL-8 labeling index was detected in the tumor areas (0.4 ± 0.2 vs 0.33 ± 0.2; p = 0, 007) but did not correlate to any of the prognostic markers: D'Amico classification (p = 0.52), Gleason score (p = 0.45), perineural (p = 0.83) and capsular invasion (p = 0.75). No correlation was found to PSA biochemical-free failure.Conclusion: IL-8 serum level was not a significant predictor of diagnosis, aggressiveness or prognosis of PCa.